Lymphocyte transformation assay for C neoformans antigen is not reliable for detecting cellular impairment in patients with Neurocryptococcosis - Rocha, Katya C.; Pinhal, Cinthia; Cavalcanti, Sonia; Vidal, Monica S. M.; Toscano, Matheus; Moraes-Vasconcelos, Dewton; Duarte, Alberto J. S.; Fonseca, Fernando L. A.; Abreu, Luiz Carlos de [UNESP]; Valenti, Vitor Engrácia [UNESP]; Grumach, Anete S. G. (Biomed Central Ltd., 2012)
Background: Cryptococcus neoformans causes meningitis and disseminated infection in healthy individuals, but more commonly in hosts with defective immune responses. Cell-mediated immunity is an important component of the immune response to a great variety of infections, including yeast infections. We aimed to evaluate a specific lymphocyte transformation assay to Cryptococcus neoformans in order to identify immunodeficiency associated to neurocryptococcosis (NCC) as primary cause of the mycosis.Methods: Healthy volunteers, poultry growers, and HIV-seronegative patients with neurocryptococcosis were tested for cellular immune response. Cryptococcal meningitis was diagnosed by India ink staining of cerebrospinal fluid and cryptococcal antigen test (Immunomycol-Inc, SP, Brazil). Isolated peripheral blood mononuclear cells were stimulated with C. neoformans antigen, C. albicans antigen, and pokeweed mitogen. The amount of H-3-thymidine incorporated was assessed, and the results were expressed as stimulation index (SI) and log SI, sensitivity, specificity, and cut-off value (receiver operating characteristics curve). We applied unpaired Student t tests to compare data and considered significant differences for p<0.05.Results: The lymphotoxin alpha showed a low capacity with all the stimuli for classifying patients as responders and non-responders. Lymphotoxin alpha stimulated by heated-killed antigen from patients with neurocryptococcosis was not affected by TCD4+ cell count, and the intensity of response did not correlate with the clinical evolution of neurocryptococcosis.Conclusion: Response to lymphocyte transformation assay should be analyzed based on a normal range and using more than one stimulator. The use of a cut-off value to classify patients with neurocryptococcosis is inadequate. Statistical analysis should be based on the log transformation of SI. A more purified antigen for evaluating specific response to C. neoformans is needed.
Keywords: Lymphocytes; Antigens; Biases; Statistical; Cryptococcus; Methods; Cryptococcus neoformans